A Buffalo on the Banks of the Mzimvubu: The Zulu Invasions of Mpondoland, 1824 and 1828 - Peires, Jeff (The Journal of Natal and Zulu history, 2021)
The conventional wisdom concerning Shaka's invasions of Mpondoland in 1824 and 1828 tends to dismiss these as cattle raids. It likewise dismisses the alignment between the 1828 invasion and Shaka's embassy to King George of Britain as nothing more than an unfortunate coincidence. Drawing in part on hitherto ignored isiXhosa-language sources, this article seeks to explain Shaka's invasion of 1828, partly in terms of his long-contemplated revenge for the failed invasion of 1824, and partly as a means to subjugate every African kingdom between himself and the Cape Colony, so that there might be only two kings in the world: King George, the king of the whites, and himself, Shaka, the king of the blacks. Only the abrupt failure of his diplomatic initiatives can explain Shaka's adverse reaction to the generally successful campaign of 1828 triggering, as it did, the near-insane and utterly disastrous northern campaign against Soshangane which directly provoked his assassination. Fully sensitive to the dangers of a 'great man' interpretation of history, the article attempts to differentiate, in Lefebvre's terms, between the 'temperament' of Shaka and the 'inner necessity' driving the evolution of the Zulu state.